Memory, War, and Dictatorship in Recent Spanish Fiction by Women - Leggott, Sarah (University Press Copublishing Division, 2015)
Memory, War, and Dictatorship in Recent Spanish Fiction by Women analyzes five novels by women writers that present women’s experiences during and after the Spanish Civil War and Franco dictatorship, highlighting the struggles of female protagonists of different ages to confront an unresolved individual and collective past. It discusses the different narrative models and strategies used in these works and the ways in which they engage with their political and historical context, particularly in the light of campaigns for the so-called recovery of historical memory in Spain (the “memory boom”) and in the broader context of memory and trauma studies. The novels that are examined in this book are Dulce Chacón’s La voz dormida (2002), Rosa Regàs’s Luna lunera (1999), Josefina Aldecoa’s La fuerza del destino (1997), Carme Riera’s La mitad del alma (2005), and Almudena Grandes’s El corazón helado (2007). These works all highlight the multiple nature of memories and histories and demonstrate the complex ways in which the past impacts on the present. This book also considers the extent to which the memories represented in these five novels are inflected by gender and informed by the gender politics of twentieth-century and contemporary Spain.